Idecabtagene vicleucel chimeric antigen receptor T-cell therapy for relapsed/refractory multiple myeloma with renal impairment - Surbhi Sidana; Lauren C. Peres; Hamza Hashmi; Hitomi Hosoya; Christopher Ferreri; Jack Khouri; Danai Dima; Shebli Atrash; Peter Voorhees; Gary Simmons; Douglas W. Sborov; Nilesh Kalariya; et al. (Haematologica, 2023)
We evaluated patients with relapsed multiple myeloma with renal impairment (RI) treated with standard of care idecabtagene vicleucel (ide-cel), as outcomes with chimeric antigen receptor (CAR) T-cell therapy are unknown in this population. RI was defined as creatinine clearance (CrCl) <50 mL/min. CrCl of <30 mL/min or dialysis dependence were defined as severe RI. The study cohort included 214 patients, 28 (13%) patients with RI, including 11 patients severe RI (dialysis, N=1). Patients with RI were older, more likely to be female and had higher likelihood of having Revised International Staging System stage 3 disease. Rates and severity of cytokine release syndrome (89% vs. 84%, grade ≥3: 7% vs. 2%) and immune effector cell-associated neurotoxicity syndrome (23% vs. 20%) were similar in patients with and without RI, respectively. Patients with RI had higher incidence of short-term grade ≥3 cytopenias, although cytopenias were similar by 3 months following CAR T-cell therapy. Renal function did not worsen after CAR T-cell therapy in patients with RI. Response rates (93% vs. 82%) and survival outcomes (median progression-free survival: 9 vs. 8 months; P=0.26) were comparable in patients with and without RI, respectively. Treatment with ide-cel is feasible in patients with RI, with a comparable safety and efficacy profile as patients without RI, with notable exception of higher short-term high-grade cytopenias.